Leitura feminista: hermenêutica de resistência da mulher a partir da casa (Mc 1.29-31) - Neves, Raimundo Clecionaldo Vasconcelos (2010)
Feminist reading: hermeneutics of woman s resistance starting from home approaches the gender relations in a social, religious, familiar, political and economic context, analyzing woman s function and the resistance process built from her home. The interpretations of the sacred text point to a woman s release from a patriarchal system, in which the man withholds all power on his children, his wife and his property. So, Jesus inaugurates a new time and he makes it from his teachings which occur in homes.